2010
DOI: 10.1002/jemt.20862
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of the 31 species of toxic and potent chinese materia medica by microscopic technique assisted by ICP‐MS analysis, part 4: Four kinds of toxic and potent mineral arsenical CMMs

Abstract: Toxic and Potent Chinese Materia Medica (T/PCMM) is a special and very important category of Chinese medicines. They have long been used in traditional medical practice and are being used more and more widely throughout the world in recent years. As there may be many fatal toxic effects caused by misusing or confusion of T/PCMM, their quality and safety control arouse increasing attention internationally. Researches on the accurate identification to ensure the safe use of T/PCMM are acquired; however, there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Microscopic studies were done by freehand cutting thin section of rhizome with platinum coated razor blade. The sections were cleared with 20% chloral hydrate solution and mounted in glycerin and observed under microscope OLYMPUS BX51 (Lin et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Microscopic studies were done by freehand cutting thin section of rhizome with platinum coated razor blade. The sections were cleared with 20% chloral hydrate solution and mounted in glycerin and observed under microscope OLYMPUS BX51 (Lin et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Quality control has always been a difficulty both in research and in the production of traditional Chinese medicine (TCM). It is also the essential foundation and key to modernizing TCM (Li et al, ; Wang et al, ; Yang et al, ). In recent years, the fingerprinting technique of high‐performance liquid chromatography (HPLC) has been recognized as a reliable, simple and efficient method for the quality control of TCMs and their derivative products (Jing et al, ; Tao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although some methods including X-ray diffraction, infrared and atomic absorption spectrometry have been applied to identification, expensive instruments are needed 10 , 11 , 12 . It is well known that microscopic techniques are fast, accurate, economical as well as simple, and have been used widely for the authentication of herbal, animal and even mineral medicines 13 , 14 , 15 . A few microscopic studies 1 , 16 on TTCMs have been reported, however, only cursory hand-drawing pictures on cross section were provided and none of them showed detailed color illustrations of the characteristics of powder.…”
Section: Introductionmentioning
confidence: 99%